Fouling threshold model of plate heat exchangers for use in the dairy industry - Mahmudiono, Trias; Widjaja , Gunawan; Mahmoud , Mustafa Z.; Garnida , Yudi; Aravindhan, Surendar; Yasin, Ghulam; Altimari , Usama Sami; Kadhim, Mustafa; Chupradit, Supat; Alhachami, Firas Rahi (Food Science and Technology, 2023)
Fouling of heat exchangers in the food industry is one of the major industrial problems because, in addition to increasing the pressure drop, increasing the cost of cleaning, and sometimes even replacing the converter, it also causes the growth of microorganisms in the deposited areas. This issue is extremely important in various industries, especially in the dairy industry. In this paper, two very important parameters, including mass temperature and fluid velocity in fouling rate, were investigated using MATLAB software. In this study, it was shown that increasing the temperature of the fluid increases the deposition. The results showed that with increasing the temperature by 20 degrees, the amount of output protein concentration decreased by 77%. Also indicates a decrease in fouling, and since the formation of fouling causes resistance on the surface of the converter plates, an increase in fouling reduces heat transfer and consequently a decrease in the overall heat transfer coefficient. The effect of increasing the concentration of dense protein in the thermal boundary layer is that the concentration of this protein affects the dimensionless number Bi and increasing it reduces the overall heat transfer coefficient compared to the pure state.